ANALYSIS OF FACTORS AFFECTING THE ADHERENCE OF TAKING ANTITUBERCULOSIS DRUGS AT PUSKESMAS KOTA MALANG - Rudy Mardianto (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Tuberculosis (TBC) is an infectious disease caused by Mycobacterium tuberculosis. The high mortality rate from TBC is associated with cases of resistance due to low adherence to medication. This study aimed to determine the effect of age, number of family members, and family support on adherence to antituberculosis drugs. The study was observational using a cross-sectional design. The subjects were 52 outpatients with tuberculosis who met the inclusion and exclusion criteria during the July-August 2022 period at Puskesmas Malang. The results of the study of the most age were 26-35 years as much as 26.92%. The highest number of family members was 3-4 people at 61.54%. Most family support was in the strong category at 86.54%. The results of the ordinal regression test showed that age had a p value of 0.045. The number of family members had a p value of 0.127. Family support had a p-value of 0.040. The conclusion was that age and family support affected medication adce with (p < 0.05). The number of family members did not affect medication adherence (p > 0.05). Age, number of family members, and family support simultaneously influenced medication adherence by 23.7%, while 76.3% were influenced by other factors that were not studied. Keywords: Adherence to taking medication, Family motivation, Tuberculosis